Penerapan Asas Keadilan Substantif dalam Penyelesaian Sengketa Pemutusan Hubungan Kerja Di Pengadilan Hubungan Industrial - Manalu, Ezrayanti; Mustafa, Afi Luthfi; Fajrin, Fauziah; Kusmiran, Adhe Clara; Simorangkir, Julius Caesar T (DPPM Universitas Pelita Bangsa, 2025)
This research aims to analyze the legal framework and judicial practice in resolving termination of employment (PHK) disputes in the Industrial Relations Court (PHI) based on the principle of substantive justice. The study employs a normative juridical approach through library research by examining laws, judicial decisions, and academic literature from 2021 to 2025 related to employment termination and industrial relations disputes. The analysis focuses on how procedural justice often dominates the PHI’s decision-making process, while substantive justice intended to protect workers’ rights has not been fully realized. Findings indicate that despite the presence of Law Number 2 of 2004 concerning Industrial Relations Dispute Settlement and the amendments in Law Number 6 of 2023 concerning Job Creation, there remains a gap between legal norms and their implementation. Factors influencing this include regulatory inconsistencies, institutional capacity, and the weak execution of court decisions. The study concludes that the application of substantive justice requires not only legal certainty but also equitable protection for both workers and employers through effective enforcement and clearer regulations to ensure fairness in every PHK dispute resolution